Stinging Nettles of Florida: Cnidoscolus - Wendy B. Zomlefer (EDIS)
Revised! HB003, a 2-page illustrated fact sheet by Wendy B. Zomlefer, describes this perennial herb with stinging hairs, milky sap, and tuberous roots — its classification, description, similar species, and toxicity. Includes references. Published by the UF Herbarium, October 2008.